The role of religious coping strategies in managing stress among Muslim adolescents - Mashudi, Nurul Atiqah; Poad, Noor Lydia; Ahmad, Noorlila (Asian Scholars Network, 2023)
Religion as a coping strategy has been acknowledged to affect how people behave in the sense of individual behavior and social community. This study examines how adolescents react to religious coping stress strategies. We employed qualitative research to explore adolescents' understanding, implementation, and views about religious coping when dealing with stress. This study was conducted in depth based on a semi-structured interview guide comprising open-ended questions through purposive sampling among Muslim adolescents between 16 and 18 in Malaysia. The interviews were analyzed to derive themes and emerging constructs related to coping strategies for managing stress. The findings of the thematic explore comprise five main themes: (1) religion as guidance; (2) religiosity level; (3) core beliefs and practices; (4) tradition, and (5) challenges in practicing religious coping strategies. The results implied that religious coping strategies and stress are continually used as self- resource and self-healing tools to overcome life pressures. As a result, promoting religiosity is a common strategy to cope with life stressors individuals face. They turned to religiosity through belief and faith, prayer, supplication, and the Quran recitation. By trusting in God, beginning one's day with positive ideas, remembrance of God, prayer, patience, and thankfulness for God for His bounty.